(untitled) (The Peerian Journal, 2023)
Today, in various sectors of the economy of rapidly developing countries, the creation of inhibitory substances used to prevent and protect metals from corrosion is an urgent problem. In the world, compounds based on nitrogen-containing ionic liquids, 2- methylbenzolammonium dehydrogen phosphate, 1,2-diammoniumbenzene hydrogen phosphate, N,N-diphenylammonium dehydrophosphate, imidazole, triazole, thiazole, indole, pyrrolidine, ammonium, piperidine and pyridine are used to reduce the corrosion of metals, the inhibitory properties of compounds are being studied, and work is underway to create effective inhibitors. The use of nitrogen-containing ionic liquids as a corrosion inhibitor gives very good results.